2022
DOI: 10.51668/bp.8322314n
|View full text |Cite
|
Sign up to set email alerts
|

The effect of life events, perceived stress, resilience, and sex on the quality of life of university students: Conditional process

Abstract: The objectives of the study were: a) to estimate the direct effect of life events on the dimensions of quality of life (Physical Health, Psychological Health, Social Relations, and Environment), b) to estimate the indirect effect of perceived stress on the relationship between events vital and the dimensions of quality of life, c) the moderation of resilience and sex on both effects in university students. 327 university students participated, 56,9% women, aged between 18 and 24 years. Perceived stress was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The relevant scientific literature shows that among the various factors that can influence a student’s perceived quality of life is perceived stress. High levels of stress correspond to low levels of quality of life [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ] in the domains of physical, psychological, interpersonal, and social health [ 86 , 87 , 90 , 91 ]. Furthermore, studies have shown that university students, especially in their first year [ 92 ], demonstrate lower levels of perceived quality of life than young working peers [ 92 , 93 , 94 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant scientific literature shows that among the various factors that can influence a student’s perceived quality of life is perceived stress. High levels of stress correspond to low levels of quality of life [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ] in the domains of physical, psychological, interpersonal, and social health [ 86 , 87 , 90 , 91 ]. Furthermore, studies have shown that university students, especially in their first year [ 92 ], demonstrate lower levels of perceived quality of life than young working peers [ 92 , 93 , 94 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These factors can have a strongly negative impact on students’ perceived health and quality of life. Finally, some studies show that the negative impact of perceived stress on quality of life could be mitigated by resilience [ 91 , 103 ] and certain coping strategies such as sport [ 104 , 105 ], religion/spirituality [ 89 , 106 ], and the ability to rely on the support of friends and family [ 89 , 107 ].…”
Section: Literature Reviewmentioning
confidence: 99%